TRANSFORMASI DIGITAL PERPAJAKAN DAN FAKTOR PERILAKU KEPATUHAN WAJIB PAJAK STUDY LITERATURE REVIEW - Sri Ayem; Dara Ayu Melinda; Aidha Pradistha Kuncoro; Febrina Nor Wahidah; Eka Saputra Pratama (Jurnal Ekonomi Dan Bisnis, 2026)
Digital transformation has brought significant changes to the taxation sector. It plays a crucial role in promoting taxpayer compliance. This article reviews the literature on the implementation of tax digitalization and its impact on taxpayer compliance behavior. The method used is Systematic Literature Review (SLR), covering 21 national and international. The study results show that digitalization, such as e-filing, e-billing, and integrated administration systems, positive influence in reporting and tax payment efficiency. It also reduces compliance costs. System quality and ease of use are key in enhancing compliance intention and practice. Besides technology benefits, psychological behavioral factors, such as trust in tax authorities, intrinsic motivation, and social norms, still play a major role. However, the main challenges found are digital literacy gaps and uneven infrastructure, especially for SMEs and rural areas. Tax digitalization helps make the tax process clearer and more trustworthy. This facilitates taxpayer compliance. This research emphasizes that the success of tax digital transformation requires synergy between technology, taxpayer behavioral aspects, and equitable digital capacity building.